2016
DOI: 10.1038/srep29371
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of physiological risk factors, oxidant-antioxidant imbalance, proteolytic and genetic variations of matrix metalloproteinase-9 in patients with pressure ulcer

Abstract: Pressure ulcer (PU) remains a common worldwide problem in all health care settings, it is synonymous with suffering. PU is a complex disease that is dependent on a number of interrelated factors. It involves multiple mechanisms such as physiological risk factors, chronic inflammation, oxidant–antioxidant imbalance and proteolytic attack on extracellular matrix by matrix metalloproteinases (MMP). Therefore, we propose that these wounds lead to molecular variations that can be detected by assessing biomarkers. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…Collagen expression was increased by curcumin treatment in TNF‐α‐treated Hs68 cells in a dose‐dependent manner. A previous study reported that MMP‐9 alters the extracellular matrix (ECM) via the cleavage of matrix components as well as collagens and has detrimental effects on wound healing . Therefore, the levels of collagen secreted from TNF‐α‐treated Hs68 cells were determined in the presence of the indicated concentrations of curcumin (0‐2.5 μM) with or without an MMP‐9 inhibitor (CAS 1177749584) using the Sircol Collagen Assay (Figure D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen expression was increased by curcumin treatment in TNF‐α‐treated Hs68 cells in a dose‐dependent manner. A previous study reported that MMP‐9 alters the extracellular matrix (ECM) via the cleavage of matrix components as well as collagens and has detrimental effects on wound healing . Therefore, the levels of collagen secreted from TNF‐α‐treated Hs68 cells were determined in the presence of the indicated concentrations of curcumin (0‐2.5 μM) with or without an MMP‐9 inhibitor (CAS 1177749584) using the Sircol Collagen Assay (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that MMP-9 alters the extracellular matrix (ECM) via the cleavage of matrix components as well as collagens and has detrimental effects on wound healing. 24 Therefore, the levels of collagen secreted from TNF-α-treated Hs68 cells were determined in the presence of the indicated concentrations of curcumin (0-2.5 μM) with or without an MMP-9 inhibitor (CAS 1177749584) using the Sircol Collagen Assay ( Figure 5D). The levels of collagen were significantly increased by curcumin treatment in TNF-α-treated fibroblasts.…”
Section: Curcumin Treatment Increased Collagen Productionmentioning
confidence: 99%
“…Different FXIII polymorphisms have also been shown to modulate and even have protective effects against ulcers progression [25]. Similarly, the SNP-1562C/T detected in the MMP-9 gene, which downregulates MMP-9 expression, has been shown to have a protective effect against pressure ulcers [28].…”
Section: Non-modifiable Risk Factorsmentioning
confidence: 99%
“…This evidence indicated that this protease could destruct the extracellular proteins, receptors and growth factors critical for PU healing (7). It has been shown that the activity of serum pro-MMP9 was elevated more in those with PU than the healthy people (34).…”
Section: Discussionmentioning
confidence: 95%